AN EMPIRICAL STUDY ON DAY OF THE WEEK EFFECT AMONG STOCKS OF SELECTED BANKS IN INDIA - Sathya Swaroop Debasish (Abhigyan, 2013)
The primary objective of the study is to investigate the existence of seasonality in stock price behavior in Indian stock market and more specifically in the banking sector. The period of the study is from 3rd November 1994 to 31st December 2010. For the purpose analysis, the study has employed daily price series that have been obtained from the official website of National Stock Exchange (NSE). The daily price series of selected nine banks were selected for this study, and used multiple regression technique to examine the significance of the regression coefficient for investigating day of week effects. It is found that all the nine selected banks evidenced day of the week effect and mostly either on Monday, Tuesday or Wednesday. Only IDBI , OBC and PNB evidenced significant Thursday effect.